Investigation of carbamazepine-Fe(III) and 10,11 dihydroxcycarbamazepine-Fe(III) interactions with spectrophotometric method [Karbamazapin -Fe(III) ve 10,11 Dihidroksikarbamazapine-Fe(III) Etkileşimlerinin Spektrofotımetrik Yöntemle İncelenmesi] - (:unkn) unknown (Turkish Pharmacists Association, 2009)
Carbamazepine (CBZ) is an antiepileptic drug, with a structure similar to imipramine. In this study, chemical interaction of carbamazepine and 10,11 dihydroxycarbamazepine (CBZ-diol) which is one of the most important metabolites of carbamazepine with Fe(III) were investigated in in-vitro media in order to examine anemia owing to iron deficiency. The data are obtained via investigation of the compounds that form complexes with iron. As a result of spectrophotometric investigation of the chemical interaction between CBZ and Fe (III) was found to occur in % 10 dioxane - water solvent medium, at the interval of pH= 2-3, at room temperature, in 5 min reaction time, when equal concentrations of CBZ and Fe (III) were used. The interaction reaction of 10,11CBZ-diol with Fe (III) was found to occur optimally in aqueous solution at room temperature, in 5 min reaction time, at the interval of pH=2-3 and concentration of CBZ two times higher than Fe (III) concentration. It is investigated that whether the interaction reaction of Fe(III)- CBZ and Fe(III)-CBZ-diol to make complexes according to Irwing-Rossoti method by potentiometry.The interaction between CBZ- Fe(III) and CBZ-diol- Fe(III) is a weak interaction reaction rather than being a reaction that forms complexes and this supports the results of spectrophotometric analysis.
Keywords: 10,11 dihydroxycarbamazepine; Carbamazepine; Chemical interaction; Fe(III); Spectrophotometry